Special articleComputer-based analysis of human skin rashes - Tyrakowski, Tomasz; Palka, Zbigniew; Żaba, Ryszard; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
In the paper we present an innovative method of computer-aided evaluation of the size of skin disease symptoms. Our method is based on the iterative algorithm, which increases the desired area starting from a single point or a set of points, until the required accuracy is achieved. The iterative method proved to be robust enough to be used on computer hardware of average efficiency, e.g. currently available PC desktops. In the text we formally define the problem of accurate measurement of skin disease symptoms and describe in detail the approach we used to solve it. We also present some experimental results obtained from the prototypal piece of software designed and implemented as a proof of concept. Although the method may require further tuning, its efficiency is high enough to make it usable as a supporting tool for specialists. We would like to describe the advantages and the resulting scientific use of this new, objective skin documentation system in clinical employment. Objective criteria may assist in distinguishing skin lesions from normal skin.